Exploring the Impact of the Academic Interactions and Social Relations of Graduate Black African Students on their Learning Experiences in Beijing - Agyenim-Boateng, Raymond (Journal of International Students, 2022)
Current research on international students has not particularly examined Black African students’ experiences in Chinese universities. This study explores the challenges encountered by African international students in China. I used semi-structured interviews of 12 Black African graduate students studying in three different universities in Beijing, China. Results indicate Chinese language, limited interaction with Chinese lecturers, and discriminatory treatment as the major challenges. Although some were ambivalent about their experiences, in general, these experiences did not produce a negative impact on their learning rather Black African students reported their overall academic experiences as being positive. The study concludes by discussing the implications of the findings for practice and recommends specific interventions to enhance Black African students’ learning experiences in Chinese universities.